Assessment of liver cranio-caudal dimensions using sonography in healthy adult Bangladeshi people - Akter, Shahinoor; Sikder, Mohammad Abdus Salam; Ananna, Samira; Chakraborty, Ananya; Jahan, Nusrat; Sharna, Najia Tahsin (International Journal of Research in Medical Sciences, 2026)
Background: Accurate assessment of liver size is an essential component of hepatobiliary evaluation and ultrasonography remains the preferred modality for routine measurement. Population-specific normative data are necessary to improve diagnostic accuracy, yet limited evidence exists for Bangladeshi adults. This study aimed to determine the cranio-caudal length (CCL) of the liver in healthy Bangladeshi adults and examine its relationship with sex, body mass index (BMI) and body surface area (BSA). Methods: A cross-sectional analytical study was conducted among 70 healthy adults (35 males, 35 females) at Sir Salimullah Medical College, Dhaka, Bangladesh. Anthropometric variables were recorded and liver CCL was measured via standardized ultrasonography using a 3.5 MHz convex transducer during maximal inspiration. Data were analyzed using t-tests and Pearson’s correlation. A p≤0.05 was considered statistically significant. Results: Males had significantly greater liver CCL (12.17±0.82 cm) than females (11.65±0.88 cm; p=0.014). BMI demonstrated no significant correlation with liver length in either sex, whereas BSA showed a significant positive correlation among females (r=0.35, p=0.04). No meaningful association was observed between liver length and BSA in males. Conclusions: Liver CCL varies significantly by sex in healthy Bangladeshi adults, while BMI shows limited predictive value. BSA exhibits a modest association with liver size among females. These findings provide population-specific reference values that may enhance the clinical interpretation of hepatic ultrasonography.